What Predicts Hospital Admissions in Community-Dwelling People With Parkinsonism?. (March 2020) - Sebastian, Roshan; Gray, William K.; Foley, Aishling; Trendall, Lydia; Oh, Doori; Hand, Annette; Dodds, Steve; McClenaghan, Elliot; Santos, Vasco Dos; Oates, Lloyd L.; Fisher, James; Walker, Richard W.
Objectives: Previous studies have looked at the reasons for hospital admission in people with parkinsonism (PwP), yet few have looked at factors that precipitate admission. Methods: People with parkinsonism with a diagnosis of idiopathic Parkinson disease of Hoehn and Yahr stage III-V and those with Parkinson plus syndromes were assessed for motor and nonmotor symptoms, quality of life, and functional performance. Logistic regression was used to investigate predictors of hospital admission over the subsequent 2 years. Results: Overall, 162 patients consented to be part of the study. Seventy-one PwP (43.8%) had at least 1 hospital admission, and 17 (10.5%) patients had 3 or more admissions to hospital. Poorer cognition, more nonmotor symptoms, poorer quality of life, slower timed-up-and-go test scores, and abnormal swallow predicted a subsequent hospital admission. Discussion: Our study emphasizes the importance of nonmotor symptoms in predicting admission. A cost–benefit analysis of early intervention to prevent admission should be considered.